The Good Outcome of Anti-Diabetic Therapy: A Proposal for Evidence Based Process Indicators - Muslim Olakunle Jamiu; Abdulganiyu Giwa; Halima Bukola Giwa; Iyabode Fatima AbulAzeez; Fullaila Onazare Aliyu (Tehran University of Medical Sciences, 2023)
ABSTRACT Background: The need to search for reliable process indicators for effectiveness of anti-diabetic therapy have been expressed in the literature. Process indicators have been described as important processes that contribute to the achievement of outcomes. Objective: This study seek to identify and propose evidence based process indicators for good outcome (effectiveness) of anti-diabetic therapy in a Nigerian University Teaching Hospital. Methods: A crossectional study using questionnaire about degree of subjects' knowledge/practice of lifestyle/dietary modification based on set criteria was conducted. Glycemic control based on latest monitoring tests and physician's remark were extracted from case note of each selected subject. Sample Size, n=1200. Subjects were selected by systematic random sampling (Sampling Interval=1). Results: Three Hundred and Thirteen (77.7%) out of 403 subjects who had good glycemic control were effects of exercise those who had excellent knowledge about signs and symptoms of hyperglycemia, beneficial effects of exercise, treatment and excellent practice of self monitoring. About 311 (77.2%) out of 403 subjects who had good glycemic control were those who had excellent knowledge about dietary modification. Almost 308 (76.4%) out of 403 subjects who had good glycemic control were those who had excellent knowledge about lifestyle modification. Three Hundred and Six  (75.9%) out of 403 subjects who had good glycemic control were those who had excellent knowledge about complications of diabetes mellitus. Significant proportion of subjects who had excellent practice of lifestyle/dietary modification had good glycemic control. Conclusion: Evidence based process indicators for good outcome (effectiveness) of anti-diabetic therapy have been identified/proposed as degree of  knowledge about signs and symptoms of hyperglycemia, complications of  diabetes mellitus, beneficial effects of exercise, treatments, dietary modification and lifestyle modification. Other process indicators identified/proposed are degree of practice of self-monitoring, lifestyle and dietary modification.